Mekanisme Komisi Pemberantasan Korupsi dalam Proses Penyadapan dilihat dari Perspektif Hak Asasi Manusia (HAM) - Jennifer Ingelyne Nussy; Harun Matayane (JURNAL BELO, 2020)
ABSTRACT Recognition and protection of a guarantee of human dignity to earn a respectable place in the eyes of the law and government. Related to the interests of law enforcement, the Corruption Eradication Commission (KPK) for the purpose of wiretapping evidence in court, while will protecting the privacyrights of suspects. Legal protections for the accused to be seen as matter of law adopted. Therefore, the protection of the privacy rights of a person to be seen in the investigation process. For the Commission to conduct wiretaps should see privacy rights as stipulated in the law and the government should establish a special set of rules that intercepts, thus providing the possibility for law enforcement has the authority to do so does not conflict with human rights.